Redox-dependent mechanisms of brain neuroprotection of rats with experimental diabetes mellitus - Temirova, Olena; Khaitovych, Mykola; Burlaka, Anatoliy; Vovk, Anastasia (ScienceRise: Pharmaceutical Science, 2018)
The aim. To investigate the efficacy regulation of redox-dependent mechanisms neuroprotection in case of various pharmacological schemes including N-acetylcysteine (NAC) and melatonin (Mel) in the brain of rats with experimental type 1 diabetes mellitus (DM 1). Methods. NAC (1.5g/kg), Mel (10 mg/kg) or their combination (NAC+Mel) where administrated to rats with induced DM 1 for 5 weeks. State of the mitochondria electron transport chain (ETC),velocity of generation superoxide radicals (SR), activity of nNOS, concentration of lactoferrin, “free iron”, methemoglobin, 8-oxoG in the cells of rats` brain were determined by electron paramagnetic resonance (EPR) method using a computerized spectrometer PE-1307 at the temperature of liquid nitrogen (T=77K). Results. During 7-week after induced DM 1, the rate of superoxide radicals (SR) generation by brains` mitochondria of rats with DM 1 was significantly higher and the activity of neuronal nitric oxide synthase (nNOS) was decreased compare to control group. The reduction in the activity of mitochondrial ETC Complex I and the growth of level 8-oxoG, concentration of "free iron" complexes, NO-FeS proteins, lactoferrin and MetHb concentration in the brain tissue of animals with DM1 were determined. Administration of all investigated pharmacological groups caused decreasing the rate of SR generation and recovering activity of nNOS by brains` mitochondria. After pharmacological intervention with NAC/Mel or NAC+Mel the levels of 8-oxoG and NO-FeS proteins were significantly decreased, activity of «free iron» complexes were normalizedinthe tissue of rats` brain with DM 1. Therapy of NAC also caused reduction level of MetHb and a combination therapy of NAC + Mel caused reduction level of lactoferrin of the rats` brain with DM 1. Conclusion. At induction of type 1 diabetes, mitochondrial ETC was damaged by products of incomplete catalysis of glucose, which manifested by a decrease in the synthesis of ATP, an increase in the level of SR, which are generated as a result of defection of the electron transport mechanism. The therapy of NAC and Mel or their combination was accompanied by the protection of the rats` brain cells with DM 1 from the toxic effect of SR, preventing disturbance of mitochondrial function that indicate neuroprotective action. NAC and Mel are perspective drugs for the prevention and treatment of diabetic neuropathy